EVALUATION OF EXPENDITURE PERFORMANCE IN THE BUDGET REALIZATION REPORT (LRA) AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY OF MAKASSAR CITY - A. Anggi Reskiamalia; Haliah; Nirwana (ZILLZELL MEDIA PRIMA, 2025)
This study aims to evaluate the performance of expenditure in the Budget Realization Report (LRA) of the Makassar City Government in the 2021-2023 budget period. Analysis is carried out on the spending performance reflected in the report, including analysis of spending variance, spending growth, spending compatibility, and spending efficiency. This study uses a quantitative descriptive approach with secondary data obtained from the documentation of the Makassar City BPKAD. The results show that the spending efficiency ratio is consistently below 100%, indicating effective budget use. In addition, the proportion of capital expenditure has increased significantly, especially in 2023, indicating a shift in government priorities in long-term investments such as infrastructure. These findings are expected to contribute to improving the quality of regional expenditure management and encourage the optimization of budget use according to the set targets.